PENGARUH DIGITAL MARKETING, STORE ATMOSPHERE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ( Studi Kasus Pada Coffee KOVII ) - Kiki Maulana Kurniawan; Nur Hidayati; Aprilia Dian Evasari (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research analyzes the influence digital marketing, store atmosphere and service quality on purchasing decisions (case study in Coffee Kovii), Kediri City. Quantitative methods were used with a sample of 85 consumers taken randomly Incidental Sampling. Data was collected through questionnaires and analyzed using validity, reliability, classical assumptions, multiple linear regression, R², t test and f test. The results of this research show that digital marketing partially has a significant effect on purchasing decisions with a significance value of 0.000 < 0.05. Store atmosphere partially has a significant effect on purchasing decisions with a significance value of 0.001 < 0.05. Service quality partially has a significant effect on purchasing decisions with a significance value of 0.000 <0.05. Whereas digital marketing, store atmosphere and service quality simultaneously has a significant effect on purchasing decisions with a significance value of 0.000 <0.05.